Implementasi Pendidikan Karakter Religius Berbasis School Culture: Studi pada Madrasah Ibtidaiyah Islamiyah Kebondalem 01 - Uspari, Nafa Alfaini; Fadli, Failasuf (PAI Fakultas Tarbiyah & Ilmu Keguruan UIN SUNA Lhokseumawe, 2024)
This study aims to explore the implementation of religious character in Madrasah Ibtidaiyah (MI) Islamiyah Kebondalem 01. The focus of the research is on the integration of religious character in the learning process, both directly and indirectly, as well as the role of teachers in shaping students' characters. A qualitative approach was used to collect and analyze data from various sources, including classroom observations, interviews with teachers, and document analysis. Research participants included teachers and students of MI Islamiyah Kebondalem 01. The results indicate that the implementation of religious character is carried out through various strategies, including extracurricular habituation, integration of religious values into various subjects, as well as teacher exemplification and guidance. Concrete steps such as scheduled religious activities, interactive religious activities, and the establishment of supportive school rules have helped shape good habits and internalized religious values in students. Based on the research findings, recommendations to maximize the implementation of religious character include: 1) Training and guidance for teachers in effective teaching methods and exemplification; 2) Development of creative and relevant learning materials related to religious values; 3) Continuous monitoring and evaluation of the implementation of religious character in classrooms; 4) Enhanced collaboration among teachers to strengthen the integration of religious values into the curriculum and daily teaching practices.